CORRELATION OF STRESS LEVEL WITH MENSTRUAL CYCLE REGULARITY IN STUDENTS OF THE FACULTY OF MEDICINE, WIDYA MANDALA CATHOLIC UNIVERSITY, SURABAYA - Debby, Amanda Aulia Citra; Budipramana, Edwin; Wattimena, Inge (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Introduction: The impact of irregular menstruation can be serious if not treated quickly. Irregular menstruation can be a sign that the cycle they are going through is not ovulating so a woman who experiences this tends to have difficulty having children. The cause of irregular menstrual cycles can be due to several factors, including hormonal changes caused by stress.Objective: To determine the relationship between stress levels and menstrual cycle regularity in female students at the Faculty of Medicine, Widya Mandala Catholic University, Surabaya.Method: The design used in this research is observational analytic with a cross-sectional study approach. The total sample for this study was 116 respondents taken using simple random sampling techniques. Data collection was carried out online using a Google form which contained a questionnaire related to stress levels and menstrual cycle regularity.Results: Most respondents experienced moderate stress, 49.1%, and 50.9% experienced irregular menstrual cycles. Based on the results of statistical tests using the Spearman correlation test, the values obtained were p = 0.000 and r = - 0.938, which shows that there is a negative and significant correlation between stress levels and menstrual cycle regularity in female students at the Faculty of Medicine, Widya Mandala Catholic University, Surabaya.Conclusion: There is a relationship between stress levels and menstrual cycle regularity in female students at the Faculty of Medicine, Widya Mandala Catholic University, Surabaya.